Study Abroad at an Ontario College: Towards More Accessible and Inclusive Programming - El Masri, Almira; Khan, Noah (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2023)
Despite Canada’s success in attracting international students to its postsecondary campuses, it sends very few domestic students abroad, and especially so from its college sector. This paper offers a brief overview of Canada’s policy approach to study abroad, literature review on students’ participation in study abroad, and outcomes of a study on students’ (perceived) barriers at a college in Ontario, Canada. Students at the college were surveyed to examine their attitudes towards study abroad participation and their perceived barriers regarding study abroad. The study found that students were overwhelmingly interested in study abroad but perceived strong barriers to participation, findings which are consistent with the literature: financial, academic, social/familial barriers, and accessibility, safety, and support concerns. These findings suggest that through expansion of national programming, coordination of provincial strategy, and inclusive, accessible policies and programming at the institutional level, more college students will be able to receive the many documented benefits of study abroad experiences.